Patterns of self-harm presentations at a Tertiary Urban Hospital in Kenya: A retrospective 5-year study (2018–2022) - Willie Njoroge; Catherine Gitau; Everline Onchari; Linnet Ongeri; Linda Khakali; Murad Khan; Zul Merali; Lukoye Atwoli; Jasmit Shah (PLoS ONE, 2025)
Introduction Self-harm represents a complex and multifaceted public health issue of global significance, exerting profound effects on individuals and communities alike. It involves intentional self-poisoning or self-injury with or without the motivation to die. Although self-harm is highly prevalent, limited research has focused on the patterns and trends of self-harm among hospital populations in low- and middle-income countries, particularly within Africa. This study aims to explore the socio-demographic and clinical profile of patients presenting with self-harm and determine the common self-harm patterns at a tertiary facility in Kenya. Methodology We carried out a descriptive retrospective study and included patients from inpatient units and outpatient settings within the Secion of Psychiatry at the Aga Khan University Hospital, Nairobi from January 1st 2018 to December 31st 2022. A data abstraction tool was used to collect data from eligible files sourced from the medical records department for all patients who met the study criteria. Summary statistics were reported as frequencies and percentages for categorical data and as means and standard deviations for continuous data. Results A total of 507 files were reviewed in the given timeframe and 497 patients were included in the analysis. Of these patients, 28.1% (n = 144) presented with self-harm. The mean age of the self-harm patients was 26.5 years (SD = 10.5) and a majority (74.3%) were female. The first point-of-contact was at the emergency department in 72.9% of the cases. A majority of them, i.e. 89.6%, reported a past psychiatric diagnosis. Based on the psychiatric diagnosis evaluation of the patients- depression was the most common diagnosis at 88.2%, followed by anxiety disorder at 27.8% and bipolar mood disorder at 17.4%. The majority of reported self-harm cases involved overdose incidents (68.8%), with self-injury accounting for 56.3% of cases. Analgesics were the most frequently reported type of overdose, followed by tricyclic antidepressants. In context of self-injury, cutting emerged as the predominant form of self-harm. Family conflict was reported to be the most common reason for self-harm at 39.6%. Conclusion This study shows a high rate of self-harm among patients with mental illness in this facility, necessitating the development of self-harm prevention and management protocols. A national registry of self-harm behavior would also help further elucidate the occurrence and mechanisms of self-harm in the population, improving the possibility for early interventions and prevention.